Electrochemical Double‐Layer Capacitor based on Carbon@ Covalent Organic Framework Aerogels. (25th October 2022) - Martín‐Illán, Jesús Á.; Sierra, Laura; Ocón, Pilar; Zamora, Félix
Abstract: High energy demand results in comprehensive research of novel materials for energy sources and storage applications. Covalent organic frameworks (COFs) possess appropriate features such as long‐range order, permanent porosity, tunable pore size, and ion diffusion pathways to be competitive electrode materials. Herein, we present a deep electrochemical study of two COF‐aerogels shaped into flexible COF‐electrodes (ECOFs) by a simple compression method to fabricate an electrochemical double‐layer capacitor (EDLC). This energy storage system has considerable interest owing to its high‐power density and long cycle life compared with batteries. Our result confirmed the outstanding behavior of ECOFs as EDLC devices with a capacity retention of almost 100 % after 10 000 charge/discharge cycles and, to our knowledge, the highest areal capacitance (9.55 mF cm −2 ) in aqueous electrolytes at higher scan rates (1000 mV s −1 ) for COFs. More importantly, the hierarchical porosity observed in the ECOFs increases ion transport, which permits a fast interface polarization (low τ0 values). The complete sheds light on using ECOFs as novel electrode material to fabricate EDLC devices. Abstract : Covalent organic framework (COFs) aerogels are shaped into flexible electrode composite by a simple compression method. It shows permanent porosity and great ion diffusion pathways appropriated for electrochemical double‐layer capacitors (EDLC). These EDLC devices demonstrated a significant areal capacitance (11.2 mF cm −2 ) with the lowest τ0 reported in COF‐based capacitors, 50 ms, and a 98 % capacitance retention over 10 000 charge/discharge cycles.